OPTIMIZATION OF YAM IN VITRO GENEBANKING: EFFECTS OF ACTIVATED CHARCOAL AND DARKNESS ON PLANTLETS OF THREE ACCESSIONS FROM BENIN - AGBIDINOUKOUN, ARNAUD (My University, 2013)
The aim of this study was to optimize the in vitro preservation of yam genetic resources through reduction of the number of subcultures. Effects of different concentrations of activated charcoal (1 g.l-1, 2 g.l-1and 3 g.l-1) and temporary darkness were tested on the in vitro morphogenesis of three beninese yam accessions (Dcr28, Dcr164 and Da93G1). Galzy glutamine was used as basis culture medium and explants were microcuttings obtained from four months old plantlets. The results indicated that the activated charcoal, alone or combined with temporary darkness has an inhibitory effect on the aerial organs formation but favors root development with a greater mean number of root shoots (9.3±1.67 with 3 g.l-1 of activated charcoal) than the subtract without activated charcoal (2.5±0.17). A significant interaction was noted between accessions and concentration of activated charcoal indicating genotypic variability from the activated charcoal effect. The different accession plantlets growing in high concentration of activated charcoal culture media combined with temporary darkness were vigorous after eight month without subculture and subsequently allow doing one subculture per year.
Keywords: Medium-term conservation; yam genetic resources; in vitro morphogenesis; activated charcoal; darkness.